Positive electrode slurry of Prussian blue compound and preparation method thereof, and positive electrode sheet

The Prussian blue compound solution was prepared by co-precipitation method and mixed with other additives to prepare the positive electrode slurry, which solved the problem of poor battery performance caused by the agglomeration of dry powder of Prussian blue compound and achieved the improvement of battery capacity and circulation ratio.

CN115275186BActive Publication Date: 2025-02-25NINGBO RONBAY LITHIUM BATTERY MATERIAL CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210980095.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-08-16
Publication Date
2025-02-25
Estimated Expiration
2042-08-16

AI Technical Summary

Technical Problem

The existing positive electrode slurry of Prussian blue compounds has agglomeration phenomenon, resulting in a difference in battery capacity and circulation ratio.

Method used

The co-precipitation method obtains a Prussian blue compound solution with a solid content of 10% to 80%, and is mixed with a binder, a conductive agent and an optional thickener to prepare a positive electrode slurry, avoiding the problem of dry powder agglomeration.

Benefits of technology

It effectively improves the battery capacity and circulation ratio, simplifies the preparation steps, reduces material costs, and is suitable for large-scale promotion and application.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115275186B_ABST
    Figure CN115275186B_ABST
Patent Text Reader

Abstract

The present application relates to the field of battery technology, and in particular to a positive electrode slurry of a Prussian blue compound, a preparation method thereof, and a positive electrode sheet. The preparation method of the positive electrode slurry of the Prussian blue compound comprises the following steps: obtaining a Prussian blue compound solution with a solid content of 10% to 80% by a coprecipitation method; placing the Prussian blue compound solution, a binder, a conductive agent, and an optional thickener in a solvent and mixing them evenly to obtain a positive electrode slurry of the Prussian blue compound. This method solves the problem that the dry powder of the Prussian blue compound is difficult to disperse into the slurry, thereby improving the capacity and initial efficiency of the battery prepared by the positive electrode slurry prepared by the method.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and in particular to a positive electrode slurry of a Prussian blue compound and a preparation method thereof, and a positive electrode sheet. Background Art

[0002] Secondary batteries represented by lithium-ion batteries have the advantages of high energy density, long cycle life and low self-discharge rate, and are widely used in electric vehicles and portable electronic devices. However, the global reserves of lithium resources are limited, and the content of lithium in the earth's crust is only 0.0065%. With the sharp increase in demand for batteries due to the development of new energy vehicles, bottlenecks on the resource side have gradually emerged, and high costs have limited the large-scale application of lithium-ion batteries. Sodium resources are very rich, with an abundance of 2.64% in the earth's crust, which is 440 times that of lithium resources. Sodium resources are widely distributed and simple to refine. Sodium has emerged as a substitute for lithium and has received more and more attention in the battery field.

[0003] Among the numerous sodium ion cathode materials, manganese-based / iron-based Prussian blue analogs (Na x M[Fe(CN)6] y ·zH2O, M=Mn, Fe) has a rigid lattice framework and a large ion channel, which is easy for sodium ion to be deintercalated, and has low raw material cost and simple synthesis method, making it one of the most promising sodium ion positive electrode materials. At present, Prussian blue compound slurries are prepared by preparing dry powder of Prussian blue compounds through oil or water methods. Small-particle Prussian blue compound materials cannot be dispersed thoroughly, and there are a large number of particles in the slurry body phase. After coating it on the current collector, the obtained pole piece has many particles and even scratches. The agglomerated particles will affect the conductive ion conduction rate, thereby increasing the impedance of the battery system, and deteriorating the battery capacity and first efficiency and other performance; and when the pole piece is severely scratched, it will cause the pole piece to be unable to be used for preparing the battery. Summary of the invention

[0004] The present application discloses a positive electrode slurry of a Prussian blue compound and a preparation method thereof, and a positive electrode plate, so as to solve the problem that the positive electrode slurry of the existing Prussian blue compound has poor battery capacity and cycle rate due to agglomeration.

[0005] In order to achieve the above objectives, this application provides the following technical solutions:

[0006] In a first aspect, the present application provides a method for preparing a positive electrode slurry of a Prussian blue compound, comprising the following steps: obtaining a Prussian blue compound solution with a solid content of 10% to 80% by a coprecipitation method; placing the Prussian blue compound solution, a binder and a conductive agent and an optional thickener in a solvent and mixing them evenly to obtain a positive electrode slurry of a Prussian blue compound.

[0007] Furthermore, the solid content of the Prussian blue compound solution is 20% to 60%.

[0008] Furthermore, the particle size of the Prussian blue compound in the Prussian blue compound solution is 0.2 um to 1 um.

[0009] Furthermore, the mass ratio of the Prussian blue compound, the conductive agent, the binder and the thickener is 70% to 97.5%: 0.5% to 10%: 0.5% to 5%: 0% to 5%.

[0010] Furthermore, the step of placing the Prussian blue compound solution, the binder and the conductive agent in a solvent and mixing them uniformly comprises the following steps:

[0011] Dissolving the binder in a solvent to obtain a binder glue solution;

[0012] Adding the conductive agent into the adhesive solution of the binder, and mixing them to obtain a conductive adhesive solution;

[0013] The Prussian blue compound solution is added into the conductive glue solution, and stirred to obtain the positive electrode slurry with a solid content of 20% to 60%.

[0014] Furthermore, the Prussian blue compound solution, the binder, the conductive agent and the thickener are placed in a solvent and mixed evenly, comprising the following steps:

[0015] Dissolving the thickener in the solvent to obtain a thickener gel solution;

[0016] Adding the conductive agent into the glue solution of the thickener, and mixing them to obtain a conductive glue solution;

[0017] Adding the Prussian blue compound solution into the conductive adhesive solution, stirring to obtain a slurry with a solid content of 30% to 60%;

[0018] The binder is added into the slurry, and after mixing, a positive electrode slurry with a solid content of 20% to 60% is obtained.

[0019] Furthermore, the Prussian blue compound solution is a Prussian white aqueous solution, and the preparation method of the Prussian white aqueous solution comprises the following steps:

[0020] A sodium sulfate solution with a concentration of 10 to 250 g / L and sodium ferrocyanide are placed in a reaction kettle, heated and kept warm at a temperature of 10 to 100° C., and then a manganese sulfate solution is added and reacted for 1 to 5 hours to obtain a Prussian white aqueous solution.

[0021] Furthermore, the mass ratio of the sodium sulfate solution to the sodium ferrocyanide is 0.2-1.

[0022] In a second aspect, the present application provides a positive electrode slurry of a Prussian blue compound prepared by the preparation method of the first aspect, wherein the solid content of the positive electrode slurry of the Prussian blue compound is 20%-60%.

[0023] In a third aspect, the present application provides a positive electrode sheet prepared using the positive electrode slurry of the Prussian blue compound of the second aspect.

[0024] The technical solution of this application produces the following beneficial effects:

[0025] The method for preparing the positive electrode slurry of the Prussian blue compound provided in the present application directly adopts the Prussian blue compound solution with a solid content of 10% to 80% obtained by coprecipitation as a raw material, and mixes with a binder, a conductive agent and an optional thickener to prepare the positive electrode slurry. Compared with the traditional preparation method, the method directly adopts the solution of the Prussian blue compound, avoiding the agglomeration problem caused by the small particle size, large specific surface area and large surface Gibbs free energy in the dry powder environment, and the particles after the dry powder agglomeration cannot be effectively dispersed by mechanical dispersion or centrifugal dispersion. The method in the present application effectively avoids the process of dry powder agglomeration, thereby solving the problem that the dry powder of the Prussian blue compound is difficult to disperse into the slurry, thereby improving the capacity and cycle rate of the battery prepared by the positive electrode slurry prepared by the method. At the same time, the method reduces the precipitation, filtration and drying steps in the process of preparing dry powder of Prussian blue compounds, and also reduces the process of redispersing the dry powder into the solution in the process of making positive electrode slurry from the dry powder of Prussian blue compounds. Therefore, the method simplifies the preparation steps, reduces material costs, and is suitable for large-scale promotion and application. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 A schematic flow chart of a method for preparing a positive electrode slurry of a Prussian blue compound provided in one embodiment of the present application;

[0027] Figure 2 This is a CCD image after the positive electrode slurry is coated on the electrode sheet in Example 1 of the present application;

[0028] Figure 3 This is a CCD image of the electrode after the positive electrode slurry is coated on the electrode in Comparative Example 1 of the present application;

[0029] Figure 4 The charge and discharge curve diagram of the button battery prepared with the positive electrode sheet in Example 1 of the present application;

[0030] Figure 5 This is a charge and discharge curve diagram of the button battery prepared with the positive electrode sheet in Comparative Example 1 of the present application. DETAILED DESCRIPTION

[0031] In order to make the purpose, technical solutions and advantages of the present application clearer, the present application will be further described in detail below in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present application.

[0032] The application scenarios described in the embodiments of the present application are intended to more clearly illustrate the technical solutions of the embodiments of the present application, and do not constitute a limitation on the technical solutions provided by the embodiments of the present application. It is known to those skilled in the art that with the emergence of new application scenarios, the technical solutions provided by the embodiments of the present application are also applicable to similar technical problems. In the description of the present application, unless otherwise specified, the meaning of "multiple" is two or more.

[0033] Currently, Prussian blue compound slurries are prepared by preparing dry powder of Prussian blue compounds through oil-based or water-based methods. Small-particle Prussian blue compound materials cannot be dispersed thoroughly, and there are a large number of particles in the slurry phase. After coating, the electrode obtained after the current collector has many particles and even scratches, which affects the electrical performance of the battery prepared using the electrode.

[0034] In view of this, the present application provides a method for preparing a positive electrode slurry of a Prussian blue compound. Figure 1 A schematic diagram of a process for preparing a positive electrode slurry of a Prussian blue compound provided in an embodiment of the present application, with reference to Figure 1 , the preparation method comprises the following steps:

[0035] S11: obtaining a Prussian blue compound solution having a solid content of 10% to 80% by a coprecipitation method;

[0036] S12: placing a Prussian blue compound solution, a binder, a conductive agent and an optional thickener in a solvent and mixing them evenly to obtain a positive electrode slurry of the Prussian blue compound.

[0037] It should be noted that the Prussian blue compound solution includes a Prussian white solution or a Prussian blue solution.

[0038] Among them, the solid content of the Prussian blue compound solution is 10% to 80%, for example, it can be 10%, 20%, 30%, 40%, 50%, 60%, 70% or 80%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0039] In one embodiment of the present application, the solid content of the Prussian blue compound solution is preferably 20% to 60%. Too high a solid content of the Prussian blue compound solution will increase the preparation cost and may cause the problem of uneven dispersion of the Prussian blue compound particles in the Prussian blue compound solution.

[0040] In one embodiment of the present application, the particle size of the Prussian blue compound in the Prussian blue compound solution is 0.2um to 1um. The particle size of the Prussian blue compound is typically but not limited to 0.2um, 0.3um, 0.4um, 0.5um, 0.6um, 0.7um, 0.8um, 0.9um, 0.99um or 1um. If the particle size of the Prussian blue compound is too large, the electrical performance of the battery composed of the positive electrode sheet prepared using the same, such as the battery capacity, will be affected.

[0041] In one embodiment of the present application, the mass ratio of the Prussian blue compound, the conductive agent, the binder and the thickener is 70% to 97.5%: 0.5% to 10%: 0.5% to 5%: 0% to 5%.

[0042] Among them, the conductive agent can be conductive carbon black (super pll, SP), KS-6 or ketchen black (ketchen black, KB); the binder can be polyacrylic acid (polyacrylic acid, PAA), polytetrafluoroethylene (poly tetrafluoroethylene, PTFE) or polymerized styrene butadiene rubber (polymerized styrene butadiene rubber, SBR); the thickener can be carboxymethylcellulose sodium (carboxymethylcellulose sodium, CMC).

[0043] In one embodiment of the present application, the binder is preferably PAA. When PAA is selected, the raw materials for configuring the positive electrode slurry of the Prussian blue compound can be a conductive agent, a binder and a Prussian blue compound solution, and the three are evenly mixed in a solvent, including the following steps:

[0044] Dissolving the binder in a solvent to obtain a binder glue solution;

[0045] Adding the conductive agent into the adhesive solution of the binder, and mixing them to obtain a conductive adhesive solution;

[0046] The Prussian blue compound solution is added into the conductive glue solution, and stirred to obtain the positive electrode slurry with a solid content of 20% to 60%.

[0047] It should be noted that, in order to fully dissolve the raw materials, the reaction solution can be fully stirred in a stirring tank, wherein the self-rotation dispersion speed is 500r to 1500r, and the revolution speed is 10r to 35r. Examples of the self-rotation dispersion speed are 500r, 600r, 700r, 800r, 900r, 1000r, 1100r, 1200r, 1300r, 1400r or 1500r. Examples of the revolution speed are 10r, 12r, 16r, 20r, 22r, 24r, 28r, 30r, 32r, 34r or 35r.

[0048] wherein, after adding the binder, stirring for 3 to 4 hours obtains a glue solution with a solid content of 1% to 5%; wherein, after the conductive agent is added to the binder glue solution, stirring for 3 to 4 hours obtains a conductive glue solution with a solid content of 3% to 40%; wherein, after the Prussian blue compound solution is added to the conductive glue solution, stirring for 1 to 4 hours obtains a positive electrode slurry with a solid content of 20% to 60%.

[0049] In one embodiment of the present application, when the binder is preferably PTFE or SBR, the raw materials for preparing the positive electrode slurry of the Prussian blue compound include a conductive agent, a binder, a thickener and a Prussian blue compound solution, and the order of adding the above raw materials is as follows:

[0050] Dissolving the thickener in the solvent to obtain a thickener gel solution;

[0051] Adding the conductive agent into the glue solution of the thickener, and mixing them to obtain a conductive glue solution;

[0052] Adding the Prussian blue compound solution into the conductive adhesive solution, stirring to obtain a slurry with a solid content of 30% to 60%;

[0053] The binder is added into the slurry, and after mixing, a positive electrode slurry with a solid content of 20% to 60% is obtained.

[0054] It should be noted that, in order to fully dissolve the raw materials, the reaction solution can be fully stirred in a stirring tank, wherein the self-rotation dispersion speed is 500r to 1500r, and the revolution speed is 10r to 35r. Examples of the self-rotation dispersion speed are 500r, 600r, 700r, 800r, 900r, 1000r, 1100r, 1200r, 1300r, 1400r or 1500r. Examples of the revolution speed are 10r, 12r, 16r, 20r, 22r, 24r, 28r, 30r, 32r, 34r or 35r.

[0055] wherein, after adding the thickener, stirring for 3 to 4 hours obtains a glue having a solid content of 1% to 5%; wherein, after the conductive agent is added to the glue of the binder, stirring for 3 to 4 hours obtains a conductive glue having a solid content of 3% to 40%; wherein, after the Prussian blue compound solution is added to the conductive glue, stirring for 1 to 4 hours obtains a positive electrode slurry having a solid content of 30% to 60%; wherein, after the binder is added to the above slurry, stirring for 1 to 2 hours obtains a positive electrode slurry having a solid content of 20% to 60%.

[0056] It is understood that the solvent type of the Prussian blue compound positive electrode slurry is not limited in this application, and the solvent in the embodiment of this application is deionized water. It should be noted that when the conductive agent is KB, the dry matter of KB needs to be mixed with the dry matter of polyvinyl pyrrolidone (PVP) and then dissolved in deionized water to obtain a uniformly mixed conductive glue.

[0057] In one embodiment of the present application, the Prussian blue compound solution is a Prussian white aqueous solution, and the preparation method of the Prussian white aqueous solution comprises the following steps:

[0058] A sodium sulfate solution with a concentration of 10 to 250 g / L and sodium ferrocyanide are placed in a reaction kettle, heated and kept warm at a temperature of 10 to 100° C., and then a manganese sulfate solution is added and reacted for 1 to 5 hours to obtain a Prussian white aqueous solution.

[0059] In the preparation method of the embodiment of the present application, in order to control the particle size of the Prussian blue compound, the reaction temperature of the sodium sulfate solution and the sodium ferrocyanide is controlled to be 10 to 100°C. The reaction temperature is exemplified by 10°C, 20°C, 30°C, 40°C, 50°C, 60°C, 70°C, 80°C, 90°C or 100°C. In the preparation method of the embodiment of the present application, in order to control the particle size of the Prussian blue compound, the reaction time after adding the manganese sulfate solution is controlled to be 1 to 5h. The reaction time is exemplified by 1h, 1.2h, 1.6h, 2h, 2.4h, 2.8h, 3.2h, 3.6h, 4h, 4.4h, 4.8h or 5h.

[0060] In one embodiment of the present application, the mass ratio of sodium sulfate solution to sodium ferrocyanide is 0.2-1, and the ratio of the two is 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9 or 1.0, etc.

[0061] In one embodiment of the present application, the concentration of the sodium sulfate solution is 10 to 250 g / L. The concentration of the sodium sulfate solution is typically but not limited to 10 g / L, 20 g / L, 30 g / L, 50 g / L, 80 g / L, 100 g / L, 120 g / L, 150 g / L, 200 g / L or 250 g / L. In one embodiment of the present application, the concentration of the manganese sulfate solution may be 150 g / L.

[0062] Based on the same inventive concept, the present application embodiment provides a positive electrode slurry of a Prussian blue compound prepared by a preparation method of various possible embodiments of the present application, wherein the solid content of the positive electrode slurry of the Prussian blue compound is 20%-60%. The solid content of the positive electrode slurry of the Prussian blue compound is typically but not limited to 20%, 25%, 30%, 35%, 40%, 50% or 60%.

[0063] Based on the same inventive concept, an embodiment of the present application also provides a positive electrode sheet prepared using the positive electrode slurry of the Prussian blue compound in the present application as a raw material.

[0064] Taking Prussian white as an example, the positive electrode slurry and positive electrode sheet prepared by the method for preparing the positive electrode slurry of the Prussian blue compound in the present application are further described in detail in combination with specific embodiments and comparative examples.

[0065] Example 1

[0066] This embodiment is a Prussian white positive electrode slurry and a positive electrode sheet prepared using the positive electrode slurry, and the preparation process thereof includes the following steps:

[0067] Add CMC and deionized water into a 2L planetary mixer, turn on the mixer, set the autorotation dispersion speed to 1000r, the revolution speed to 25r, and the stirring time to 3h to obtain a glue solution with a solid content of 2%;

[0068] Add the solution obtained by mixing the dry matter of KB and PVP to the glue solution obtained in the previous step, turn on the stirrer, rotate at a speed of 1000r, rotate at a speed of 25r, stir for 4h, and stir to prepare a conductive glue solution with a solid content of 6%;

[0069] Add the sodium ferromanganese Prussian white aqueous solution prepared by the coprecipitation method into the conductive adhesive solution, turn on the stirrer, rotate at a speed of 1500r, rotate at a speed of 30r, stir for 2h, and stir to form a slurry with a solid content of 45%;

[0070] Add SBR to the slurry obtained in the previous step, turn on the stirrer, set the self-rotation dispersion speed to 500r, the revolution speed to 15r, and the stirring time to 1h, and stir evenly to obtain a sodium electric manganese iron Prussian white slurry suitable for coating.

[0071] The prepared sodium electric manganese iron Prussian white slurry was evenly coated on a 16um thick aluminum foil current collector, and the single-sided surface density of the coating was 5mg / cm 2 Place the coated electrode in a vacuum oven at 175℃ and dry for 20 hours. Take a small amount of the dried positive electrode for CCD testing to confirm the uniformity of the slurry dispersion. Then take the electrode for cutting and roll pressing with a roller machine. The compaction density of the electrode after rolling is 1.5g / cm 3 Then, a punching machine was used to punch out discs with a diameter of 15 mm. The homemade positive electrode sheet was used as the positive electrode, the lithium sheet was used as the negative electrode, the Celgard2400 polypropylene microporous membrane was used as the separator, and 1 mol / L LiPF6 / EC:EMC:DMC=1:1:1 was used as the electrolyte. The cells were assembled into CR2430 button cells in an argon-filled glove box with water and oxygen contents below 0.1 ppm.

[0072] Example 2

[0073] This embodiment is a Prussian white positive electrode slurry and a positive electrode sheet prepared using the positive electrode slurry, and the preparation process thereof includes the following steps:

[0074] Add PAA and deionized water into a 2L planetary mixer, turn on the mixer, set the autorotation dispersion speed to 1000r, the revolution speed to 25r, and the stirring time to 1h to obtain a glue solution with a solid content of 5%;

[0075] Add the solution obtained by mixing the dry matter of KB and PVP to the glue obtained in the previous step, turn on the stirrer, rotate at a speed of 2000r, rotate at a speed of 25r, stir for 4h, and stir to prepare a conductive glue with a solid content of 10%;

[0076] The aqueous solution of sodium electric manganese iron Prussian white material prepared by co-precipitation method is added into the conductive adhesive solution, and the stirrer is turned on with a self-rotation dispersion speed of 2500r, a revolution speed of 25r, and a stirring time of 3h. After stirring evenly, a sodium electric manganese iron Prussian white slurry with a solid content of 38% suitable for coating is obtained.

[0077] The prepared sodium electric manganese iron Prussian white slurry was evenly coated on a 16um thick aluminum foil current collector, and the single-sided surface density of the coating was 4.5mg / cm 2 Place the coated electrode in a vacuum oven at 170°C and dry for 24 hours. Take a small amount of the dried positive electrode for CCD testing to confirm the uniformity of the slurry dispersion. Then take the electrode for cutting and roll pressing with a roller machine. The compaction density of the electrode after rolling is 1.3g / cm 3Then, a punching machine was used to punch out discs with a diameter of 15 mm. The homemade positive electrode sheet was used as the positive electrode, the lithium sheet was used as the negative electrode, the Celgard2400 polypropylene microporous membrane was used as the separator, and 1 mol / L LiPF6 / EC:EMC:DMC=1:1:1 was used as the electrolyte. The cells were assembled into CR2430 button cells in an argon-filled glove box with water and oxygen contents below 0.1 ppm.

[0078] Examples 3-6 and Comparative Examples 1-4

[0079] Examples 3-6 and Comparative Examples 1-4 are respectively positive electrode slurries of Prussian white and positive electrode sheets prepared using the positive electrode slurries. The specific preparation processes of Examples 3-6 and Comparative Examples 1-3 can refer to the preparation of Example 1, and the specific preparation process of Comparative Example 4 can refer to the preparation of Example 2. The difference is that the raw materials for configuring the positive electrode slurry are different, and the specific composition is listed in Table 1. The positive electrode slurry in the above examples and comparative examples was tested for slurry fineness by a scraper fineness meter, and the test results are listed in Table 1.

[0080] Table 1

[0081]

[0082] Combination Figures 2 to 3 Explain the data in Table 1. Figure 2 This is the CCD image after the positive electrode slurry is coated on the electrode in Example 1 of the present application. Figure 3 This is the CCD image after the positive electrode slurry is coated on the electrode sheet in Comparative Example 1 of this application, refer to Figure 2 and Figure 3 , Figure 2 The pole pieces are smooth and there is no agglomeration to the naked eye. Figure 3 There are agglomerated particles visible to the naked eye in the electrode pieces. The fineness of the sodium electric manganese iron Prussian white positive electrode slurry in Example 1 is 15um, and the fineness of the positive electrode slurry in Comparative Example 1 is 125um. It can be seen that the fineness of the sodium electric manganese iron Prussian white aqueous solution obtained by the co-precipitation method is significantly lower than that of the positive electrode slurry obtained by configuring the sodium electric manganese iron Prussian white powder.

[0083] According to the data of Example 1 and Comparative Example 2, Example 2 and Comparative Example 4 in Table 1, when the solid content of the sodium electric manganese iron Prussian white aqueous solution is 85%, the slurry fineness of the positive electrode slurry prepared therefrom is significantly increased relative to the fineness of the positive electrode slurry prepared from the sodium electric manganese iron Prussian white aqueous solution with a solid content of 40%.

[0084] According to the data of Example 1 and Implementation 3-4 in Table 1, when the particle size of the sodium electric manganese iron Prussian white aqueous solution is 0.6um, its solid content is 55% and 45%, and the slurry fineness of the prepared positive electrode slurry is 28um and 20um, which are both greater than the slurry fineness of the positive electrode slurry prepared from the sodium electric manganese iron Prussian white aqueous solution with a solid content of 40%.

[0085] According to the data of Example 1 and Implementation 5-6 in Table 1, when the solid content of the sodium electric manganese iron Prussian white aqueous solution is 40%, when the particle size is 0.6um, the fineness of the positive electrode slurry prepared therefrom is 15um, when the particle size is 0.8um, the fineness of the positive electrode slurry prepared therefrom is 27um, and when the particle size is 0.9um, the fineness of the positive electrode slurry prepared therefrom is 30um.

[0086] The positive electrode sheets in the above embodiments and comparative examples were used to prepare corresponding button batteries. The assembled button batteries were subjected to performance tests. Charge and discharge tests were performed at a rate of 0.1C in the voltage range of 2.0V to 4.0V. The specific test results are listed in Table 2.

[0087] Table 2

[0088] Serial number First discharge capacity (mAh / g) First efficiency Example 1 163 96% Comparative Example 1 70 94% Comparative Example 2 145.2 94.5% Comparative Example 3 155.4 93.9% Example 2 161.2 95.5% Comparative Example 4 144.4 93.5% Example 3 160.2 94.8% Example 4 161.6 96.2% Example 5 160.8 95.1% Example 6 159.5 94.4%

[0089] In order to further understand the data in Table 2, Figure 4 and 5 To explain, Figure 4 This is a charge and discharge curve diagram of a button cell made of the positive electrode sheet in Example 1 of the present application. Figure 5 The charge and discharge curve of the button battery prepared by the positive electrode sheet in Comparative Example 1 of this application is shown in FIG. Figure 4 and Figure 5 As can be seen from the data in Table 2, the first discharge capacity of the battery prepared with the positive electrode sheet in Example 1 is 163 mAh / g, and the first discharge capacity of the battery in Comparative Example 1 is 70 mAh / g. It can be seen that the button battery prepared with the sodium electric manganese iron Prussian white aqueous solution has a higher first discharge capacity than the button battery prepared with the positive electrode slurry prepared with the sodium electric manganese iron Prussian white powder.

[0090] According to the data of Examples 1-4 and Comparative Example 2 in Table 2, it can be seen that, compared with the sodium electric manganese iron Prussian white aqueous solution with a solid content of 85%, the first discharge capacity and first efficiency of the battery composed of the pole pieces prepared by the sodium electric manganese iron Prussian white aqueous solution with a solid content of 40%, 45%, and 55% are higher;

[0091] Combining the comparative data of Table 1 and Table 2, it can be seen that the positive electrode slurry of the Prussian blue compound prepared by the preparation method in the embodiment of the present application has a slurry fineness that is much smaller than the positive electrode slurry prepared by configuring the sodium electric manganese iron Prussian white powder, and the first discharge capacity and first efficiency of the battery prepared using the positive electrode slurry are significantly improved.

[0092] The above are only specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any technician familiar with the technical field can easily think of changes or substitutions within the technical scope disclosed in the present application, which should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.

Claims

1. A method for preparing a positive electrode slurry of a Prussian blue compound, characterized in that: The steps include: A Prussian blue compound solution with a solid content of 10% to 80% is obtained by a coprecipitation method; The Prussian blue compound solution, the binder and the conductive agent are placed in a solvent and mixed evenly to obtain a positive electrode slurry of the Prussian blue compound; or the Prussian blue compound solution, the binder, the conductive agent and the thickener are placed in a solvent and mixed evenly to obtain a positive electrode slurry of the Prussian blue compound; The particle size of the Prussian blue compound in the Prussian blue compound solution is 0.2um-1um.

2. The preparation method according to claim 1, characterized in that: The solid content of the Prussian blue compound solution is 20% to 60%.

3. The preparation method according to claim 1, characterized in that: The mass ratio of the Prussian blue compound, the conductive agent, the binder and the thickener is 70% to 97.5%: 0.5% to 10%: 0.5% to 5%: 0% to 5%.

4. The preparation method according to claim 1, characterized in that: The step of placing the Prussian blue compound solution, the binder and the conductive agent in a solvent and mixing them evenly comprises the following steps: Dissolving the binder in the solvent to obtain a glue solution of the binder; Adding the conductive agent into the adhesive solution of the binder, and mixing them to obtain a conductive adhesive solution; The Prussian blue compound solution is added into the conductive adhesive solution, and stirred to obtain a positive electrode slurry with a solid content of 20% to 60%.

5. The preparation method according to claim 1, characterized in that: The step of placing the Prussian blue compound solution, the binder, the conductive agent and the thickener in a solvent and mixing them evenly comprises the following steps: Dissolving the thickener in the solvent to obtain a glue solution of the thickener; Adding the conductive agent into the glue of the thickener, and mixing them to obtain a conductive glue; Adding the Prussian blue compound solution into the conductive adhesive solution, stirring to obtain a slurry with a solid content of 30% to 60%; The binder is added into the slurry, and after mixing, a positive electrode slurry with a solid content of 20% to 60% is obtained.

6. The preparation method according to any one of claims 1 to 5, characterized in that: The Prussian blue compound solution is a Prussian white aqueous solution, and the preparation method of the Prussian white aqueous solution comprises the following steps: A sodium sulfate solution with a concentration of 10 to 250 g / L and sodium ferrocyanide are placed in a reaction kettle, heated and kept warm at a temperature of 10 to 100° C., and then a manganese sulfate solution is added to react for 1 to 5 hours to obtain the Prussian white aqueous solution.

7. The preparation method according to claim 6, characterized in that: The mass ratio of the sodium sulfate solution to the sodium ferrocyanide is 0.2-1.

8. A positive electrode slurry of a Prussian blue compound prepared by the preparation method according to any one of claims 1 to 7, characterized in that: The solid content of the positive electrode slurry of the Prussian blue compound is 20% to 60%.

9. A positive electrode sheet, characterized in that: The positive electrode slurry is prepared using the Prussian blue compound as claimed in claim 8.

Citation Information

Patent Citations

  • Mixing preparation method of pulp of lithium ion battery

    CN101694872A

  • High-compaction and high-stability high-nickel cathode material and preparation method thereof, and lithium ion battery

    CN110010889A